2022
DOI: 10.1063/5.0107557
|View full text |Cite
|
Sign up to set email alerts
|

Role of defects in ultra-high gain in fast planar tin gallium oxide UV-C photodetector by MBE

Abstract: We report ultra-high responsivity of epitaxial (Sn x Ga 1−x ) 2 O 3 (TGO) Schottky UV-C photodetectors and experimentally identified the source of gain as deep-level defects, supported by first principle calculations. Epitaxial TGO films were grown by plasma-assisted molecular beam epitaxy (PAMBE) on (-201) oriented n-type β -Ga 2 O 3 substrates. Fabricated vertical Schottky devices exhibited peak responsivities as high as 3.5×10 4 A/W at -5 V applied bias under 250 nm illumination with sharp cut-off shorter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, based on this theoretical model, the reduced height (δ) of the effective Schottky potential controlled by the local hole trapping and gate voltage effects will significantly improve the comprehensive transport characteristic of the nanodotsintegrated device, as confirmed by the measured I-V curve in figure 4(b). Furthermore, Mukhopadhyay et al have demonstrated that the hole trapping could effectively regulate the Fermi level of a semiconductor film, which might further reduce the Schottky barrier potential at the metal/semiconductor interface [57]. In this case, the electron tunneling effect was going to work during electrical transport process, which could obviously increase the dark current of a Schottky-barrier photodetector.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on this theoretical model, the reduced height (δ) of the effective Schottky potential controlled by the local hole trapping and gate voltage effects will significantly improve the comprehensive transport characteristic of the nanodotsintegrated device, as confirmed by the measured I-V curve in figure 4(b). Furthermore, Mukhopadhyay et al have demonstrated that the hole trapping could effectively regulate the Fermi level of a semiconductor film, which might further reduce the Schottky barrier potential at the metal/semiconductor interface [57]. In this case, the electron tunneling effect was going to work during electrical transport process, which could obviously increase the dark current of a Schottky-barrier photodetector.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, annealing the heterostructures may not necessarily lead to only a reduction in the interfacial defects but can also significantly alter the interface chemistry. This particular combination of n–n materials for solar-blind photodetection can be further improved by using various strategies such as defect engineering where the oxygen vacancy defects in the system may be optimized using different oxygen partial pressures to achieve a better performance or via ozone treatment. Another way to improve upon the device performance could be the use of interface engineering such as the addition of a high mobility layer like graphene at the interface for a quicker extraction of charge carriers, functionalizing with other materials, etc. For heterostructure-based PDs, tweaking the interface can surely change how the detectors perform, and this study shows how the n–n heterojunction interface between two different materials plays a key role in improving the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the device structure remold, Vieira et al [152] improved the photo-sensing performance of the Ga 2 O 3 Schottky photodiode by coupling two planar diodes; the I photo increased as much as 186 times, and the R and D * also improved significantly. In addition, from two points of materials and devices, the modification of the Schottky barrier interface (concerning the basic feature of Schottky photodiode) [153] and the study on defect physics (concerning trapping) in Ga 2 O 3 [154][155][156][157][158][159] contribute to the boom in next-generation functional DUV photodetectors in actual applications [4,160,161]. In a photodetector, mid-bandgap donor/acceptor levels caused by defects play a role in trapping holes and thus enhance the photoconductive gain [103,158].…”
Section: Recent Advancesmentioning
confidence: 99%
“…In addition, from two points of materials and devices, the modification of the Schottky barrier interface (concerning the basic feature of Schottky photodiode) [153] and the study on defect physics (concerning trapping) in Ga 2 O 3 [154][155][156][157][158][159] contribute to the boom in next-generation functional DUV photodetectors in actual applications [4,160,161]. In a photodetector, mid-bandgap donor/acceptor levels caused by defects play a role in trapping holes and thus enhance the photoconductive gain [103,158]. Meanwhile, for Schottky photodiodes, the hole trapping at these deep-level defects [154] in the space charge region could be responsible for the exponential increase of I photo by lowering the Schottky barrier, and electron tunneling will happen due to the lowering of the SBH and the thinning of the Schottky barrier width [158].…”
Section: Recent Advancesmentioning
confidence: 99%
See 1 more Smart Citation